(untitled) (Research, Society and Development, 2022)
Endometriosis is a chronic gynecological condition of inflammatory origin, multifactorial that affects mainly women in the fertile age, the development of the disease occurs outside the woman’s uterine cavity, and may arise in the pelvic region or in other organs such as diaphragm, lung, bladder, intestine, abdominal wall, stomach and ovaries, and between 30 and 50% of women suffer from infertility due to the disease. The present study has as its main objective to clarify how a balanced diet through the supply of foods with anti-inflammatory and antioxidant properties can have a beneficial action on the development and reduction of the clinical symptoms of endometriosis. This is a literature review research, in which original and review scientific articles, doctoral theses, and legal documents were analyzed. Studies have shown that several factors can enhance or increase the development of this disease, including: lifestyle and diet quality. Maintaining a balanced diet based on natural foods, vitamins and minerals with antioxidant and anti-inflammatory properties is a positive strategy in the physiological processes of the disease, reducing the clinical symptoms and regression of endometriosis. Thus, it is shown how important the nutritionist is in the guidance on food choices according to the individual needs of each patient.